An Ultrafast N-Glycoproteome Analysis Method Using Thermoresponsive Magnetic Fluid-Immobilized Enzymes - Fan, Zhiya; Liu, Tong; Zheng, Fei; Qin, Weijie; Qian, Xiaohong (Frontiers in Chemistry, 2021)
N-Glycosylation is one of the most common and important post-translational modification methods, and it plays a vital role in controlling many biological processes. Increasing discovery of abnormal alterations in N-linked glycans associated with many diseases leads to greater demands for rapid and efficient N-glycosylation profiling in large-scale clinical samples. In the workflow of global N-glycosylation analysis, enzymatic digestion is the main rate-limiting step, and it includes both protease digestion and peptide-N4–(N-acetyl-beta-glucosaminyl) asparagine amidase (PNGase) F deglycosylation. Prolonged incubation time is generally required because of the limited digestion efficiency of the conventional in-solution digestion method. Here, we propose novel thermoresponsive magnetic fluid (TMF)-immobilized enzymes (trypsin or PNGase F) for ultrafast and highly efficient proteome digestion and deglycosylation. Unlike other magnetic material-immobilized enzymes, TMF-immobilized enzymes display a unique temperature-triggered magnetic response behavior. At room temperature, a TMF-immobilized enzyme completely dissolves in an aqueous solution and forms a homogeneous system with a protein/peptide sample for efficient digestion but cannot be separated by magnetic force because of its excellent water dispersity. Above its lower critical solution temperature (LCST), thermoflocculation of a TMF-immobilized enzyme allows it to be easily recovered by increasing the temperature and magnetic force. Taking advantage of the unique homogeneous reaction of a TMF-immobilized enzyme, both protein digestion and glycopeptide deglycosylation can be finished within 3 min, and the whole sample processing time can be reduced by more than 20 times. The application of a TMF-immobilized enzyme in large-scale profiling of protein N-glycosylation in urine samples led to the successful identification of 2,197 N-glycopeptides and further demonstrated the potential of this strategy for fast and high-throughput analysis of N-glycoproteome in clinical samples.